Learning science through computer games and simulations - National Research Council (U.S.). Committee on Science Learning: Computer Games, Simulations, and Education; Honey, Margaret; Hilton, Margaret L.; National Academies Press (U.S.) (Washington, D.C. : National Academies Press, 2011)
At a time when scientific and technological competence is vital to the nation's future, the weak performance of U.S. students in science reflects the uneven quality of current science education. Although young children come to school with innate curiosity and intuitive ideas about the world around them, science classes rarely tap this potential. Many experts have called for a new approach to science education, based on recent and ongoing research on teaching and learning. In this approach, simulations and games could play a significant role by addressing many goals and mechanisms for learning science: the motivation to learn science, conceptual understanding, science process skills, understanding of the nature of science, scientific discourse and argumentation, and identification with science and science learning. To explore this potential this book reviews the available research on learning science through interaction with digital simulations and games. It considers the potential of digital games and simulations to contribute to learning science in schools, in informal out-of-school settings, and everyday life. The book also identifies the areas in which more research and research-based development is needed to fully capitalize on this potential. It will guide academic researchers, developers, publishers, and entrepreneurs from the digital simulation and gaming community, and education practitioners and policy makers toward the formation of research and development partnerships that will facilitate rich intellectual collaboration. Industry, government agencies and foundations will play a significant role through start-up and ongoing support to ensure that digital games and simulations will not only excite and entertain, but also motivate and educate.
Includes bibliographical references (p. 129-148).
Also available in Open Book format via the National Academies Press home page.
d
Keywords: Science -- Study and teaching (Elementary); Science -- Study and teaching (Secondary); Science -- Computer-assisted instruction; Interactive multimedia